Non-linear Effect of Islamic Banks' Liquidity Risk to Financial Stability; Evidence from the Indonesian Banking Industry - Fakhrunnas, Faaza (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2023)
Liquidity risk is a pivotal aspect that determines the soundness of financial performance in the banking system. Therefore, the study aims to examine the influence of Islamic banks' liquidity risk on banking stability. Using time series data ranging from 2004m1 to 2022m8, the study adopts a non-linear autoregressive distributed lag (NARDL) approach to examine the influence of liquidity risk on financial stability in the Indonesian banking sectors. The result of the study reveals that it has a non-linear and asymmetric relationship between liquidity risk and financial stability in the banking system. In the short run, an additional increase/decrease in the change of liquidity risk negatively affects financial stability. In addition, the long-run relationship shows that only an additional increase in change has a negative and significant relationship to financial stability. The COVID-19 pandemic also becomes a significant determinant that affects financial stability in the long-run relationship. The findings of the study imply that the Indonesian financial authorities should set suitable regulations to mitigate and address the issue of Islamic banks' liquidity risk, particularly in anticipating its non-linear and asymmetric impact on financial stability.